Diversity of Japanese consumers' requirements, sensory perceptions, and eating preferences for meat. (9th March 2022) - Sasaki, Keisuke
Abstract: Japanese consumers are generally characterized as preferring high marbling in beef and pork and choosing domestic products. However, the Japanese food market is not homogenous. Understanding the diversity of Japanese consumers will provide benefits for the optimization of meat production and distribution in Japan. This article focuses on three factors affecting purchasing decisions and eating satisfaction, namely, requirements, sensory perception, and eating preferences, in order to understand the diversity of Japanese consumers in a simplified manner. Diversity was observed in Japanese consumers in all three of these factors (requirements, perception, and preference) using a questionnaire survey, sensory and biological procedures, and an eating preference test. These diversities are due to not only sociodemographic characteristics but also biological and physiological factors, background culture, and individual attitudes and criteria. Although consumer variation based on sociodemographic characteristics is of course important, it is equally important to understand diversity by focusing on the individual differences among consumers.